Perbandingan Hasil Belajar Biologi yang Diajar Menggunakan Model Cooperative Integrated Reading And Composition (CIRC) dengan Model Pembelajaran Langsung Berdasarkan Keterampilan Berpikir Kritis Siswa Kelas X SMA Negeri 4 PALU - Muhamad Erwin; Andi Tanra Tellu; I Nengah Kundera (Universitas Tadulako, 2015)
The study aimed, to describe the difference of students’ learning outcomes of (1) cooperative integrated reading and composition (CIRC) and direct instruction on biology subject, (2) describe the different of critical thinking high level and the lowest by student learning outcomes. This study using quasi experiment. All students in grade 10 who enrolled 2013-2014 would become research subject. The sample of this research consisted of two classes: X MIA5 and X MIA6. The results showed that the comparison between the two learning models can be seen with the magnitude of the significant probability value < 0.05. There is also a difference between the learning outcomes of students who have highest critical thinking skills with students who have the lowest, where the average of each value 55.63 and 38.42 or significant probability value < = 0.05. It could be concluded, that the student who have the highest critical-thinking skills were taught by using both learning models was better learning-outcomes than the lowest.